2018
DOI: 10.5603/fm.a2018.0004
|View full text |Cite
|
Sign up to set email alerts
|

Effects of nicotine administration in rats on MMP2 and VEGF levels in periodontal membrane

Abstract: Nicotine is associated with increased incidence of periodontal disease and poor response to therapy. This article aimed at identifying the expression of Matrix metalloproteinases-2 (MMP2) and Vascular endothelial growth factor (VEGF) proteins on extracellular matrix, fibrous distribution and angiogenetic development in periodontitis caused by nicotine effects on periodontal membrane. In this experimental study, the groups were divided into nicotine and control groups. While the nicotine groups in rats (n=6) we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 39 publications
(41 reference statements)
0
11
0
Order By: Relevance
“…Nicotine has an additive effect on human gingival fibroblast-mediated collagen degradation when combined with the presence of P. gingivalis 31 . Deveci et al 32 found that nicotine reduces the production of MMPs, disrupts collagen synthesis and causes periodontitis in rats. They observed that nicotine increases periodontitis by disrupting the periodontal membrane and prevents the anchorage of teeth in the dental alveoli by disrupting the epithelial structure.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nicotine has an additive effect on human gingival fibroblast-mediated collagen degradation when combined with the presence of P. gingivalis 31 . Deveci et al 32 found that nicotine reduces the production of MMPs, disrupts collagen synthesis and causes periodontitis in rats. They observed that nicotine increases periodontitis by disrupting the periodontal membrane and prevents the anchorage of teeth in the dental alveoli by disrupting the epithelial structure.…”
Section: Resultsmentioning
confidence: 99%
“…Nicotine, which is the major ingredient of cigarette smoke, up-regulates MMP-1, MMP-2 and MMP-3 gene expression in arterial smooth muscle cells, vascular endothelial cells, periodontal ligament fibroblasts and osteoclasts. Nicotine administration also causes a change in fibroblast activity due to the change of collagen fiber synthesis and decreased MMP2 expression 32 .…”
Section: Resultsmentioning
confidence: 99%
“…2016, Deveci et al . 2018). The period of 28 days of nicotine application was sufficient to observe its effects on alveolar bone (Liu et al .…”
Section: Discussionmentioning
confidence: 99%
“…2013, Deveci et al . 2018). In this study, the IP injections were initiated 7 days before pulp access, to simulate the induction of apical periodontitis in an organism already exposed to nicotine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation